Correlation Between Ionic Mobility and Plastic Flow Events in NaPO3-NaCl-Na2SO4 Glasses - Poletto Rodrigues, Bruno; Limbach, Rene; Buzatto de Souza, Gabriel; Ebendorff-Heidepriem, Heike; Wondraczek, Lothar (Frontiers in Materials, 2019)
We report on the evolution of the mechanical and electrical properties of sodium metaphosphate glasses with addition of sodium sulfate or sodium chloride. The addition of these two sodium salts converts the medium-range order of our glasses from 2D phosphate chains to a mixed 1D + 2D network similar to ionic glasses, while the short-range order of the phosphate units remains unaffected. Replacing the phosphate units by chloride ion monotonically decreases the glass transition temperature, but enhances the Young’s modulus and moderately increases the ionic conductivity. On the other hand, the sulfate group decreases the glass transition temperature as well, though the Young’s modulus remains constant, while the ionic conductivity strongly increases. The changes in conductivity are related to the enhancement of the ionic mobility in these glasses, which in turn affect the size and distribution of the plastic events taking place during indentation-driven deformation.